"I'm that bitch": on queerness and the catwalk. Issue 2 (3rd April 2017) - Moore, Madison
Abstract: Within the world of queer performance, being "that bitch" is about having an exacting, unquestionable creative juice and asserting yourself through performance and style. It's not about asking for permission to exist but about existing anyway, right now, and on terms you decide for yourself. For queer people of color, being "that bitch" is about queer livelihood and ethical self-making, particularly when you are forced to exist in a world with norms that were not created with you in mind in the first place. The ideal space to prove you're "that bitch" is the catwalk, particularly in the voguing community.